1996
DOI: 10.1002/(sici)1097-4628(19960926)61:13<2245::aid-app1>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of PMMA/polyoxide blends containing graft-copolymer compatibilizers by using NMR, SEM, and thermal analysis

Abstract: SYNOPSISThe effects of blend compatibility caused by compatibilizing agents were studied by microscopy, thermal analysis, and nuclear magnetic resonance (NMR) spectroscopy (carbon-13 NMR spectra and proton spin-lattice relaxation time) of homopolymers and polymer blends. In this study the results obtained by all measurements are discussed in terms of molecular mobility and compatibility, as a consequence of changes in the microdomains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In recent years, great attention was paid to graft copolymers, because of their unique molecular architecture, particular morphology and increased number of applications. They have been widely used for the preparation of compatibilizers for polymer blends, membranes for separation of gases or liquids, hydrogels, drug deliverers, thermoplastic elastomers, etc. A number of methods have been employed for their synthesis, such as the macromonomer method, radiation-induced polymerization, ring-opening olefin methathesis polymerization, polycondensation reaction and iniferter-induced polymerization .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, great attention was paid to graft copolymers, because of their unique molecular architecture, particular morphology and increased number of applications. They have been widely used for the preparation of compatibilizers for polymer blends, membranes for separation of gases or liquids, hydrogels, drug deliverers, thermoplastic elastomers, etc. A number of methods have been employed for their synthesis, such as the macromonomer method, radiation-induced polymerization, ring-opening olefin methathesis polymerization, polycondensation reaction and iniferter-induced polymerization .…”
Section: Introductionmentioning
confidence: 99%
“…The moderate levels of ionic conductivity reported for SPEs based on commercial PEO are still considered inadequate for many electrochemical applications, however the advantages they offer as solid-state components, their thermal, electrochemical and physical stability and their potential as multi-functional components in devices, continue to provide motivation for further development (1,2). Many different approaches have been used to improve the properties of PEO-based electrolytes by modifying network architecture (3)(4)(5)(6)(7)(8)(9). Poly(trimethylene carbonate), designated as pTMC, is a high molecular weight amorphous elastomer with a T g close to room temperature (-18ºC) with excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, no such studies on this system have been reported, but many blends of PET with HDPE [6,7], ABS [8], PS [5], and PA [9,10] were studied in the past for the improvement in impact and modulus. Blends of PMMA with PP [11], PEO [12], and natural rubber [13] showed improvement in the impact strength. Both the polymers are transparent and polar; PET has the ester repeat unit in the backbone while PMMA has the ester repeat unit in the side chain.…”
Section: Introductionmentioning
confidence: 99%